Surfacing flux-cored wire capable of being hardened through work
By using a specific composition of surfacing flux-cored welding wire, combined with components such as high-carbon ferrochromium, ferromolybdenum and titanium additives, fine in-situ titanium carbide and solid solution Mo and Cr are formed to solve the problem of the hammer head of the hammer crusher The problem of insufficient hardness and wear resistance in high-impact environments achieves a significant increase in hardness and wear resistance of the welding layer.
Patent Information
- Application Number
- CN202411853954.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-17
AI Technical Summary
In the high impact and high stress conditions, it is difficult to achieve comprehensive performance of both good wear resistance and high hardness.
A work-hardenable flux cored welding wire is used, which is composed of high carbon ferrochrome, 75# ferrosilicon, electrolytic manganese, ferromolybdenum, titanium additives, arc stabilizer and rare earth additives. Through specific components According to the proportion and welding process, fine in-situ titanium carbide and solid solution Mo and Cr are formed to improve the hardness and wear resistance of the cladding metal.
After surfacing on the high manganese steel base material, the welding wire can significantly improve the hardness (5HRC-15HRC) and wear resistance in high-impact and high-stress environments, extending the service life of the hammer head.
Smart Images

Figure CN119328358A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of welding wires, and in particular relates to a hardening cladding flux-cored welding wire. Background Art
[0002] The hammer of the crusher is a vulnerable and consumable part of the crusher. When the hammer rotates at high speed, it collides violently with the falling materials, thus crushing the materials. The hammer is in a state of high impact and high stress abrasive wear, and its wear and tear is very rapid. The hammer needs to be repaired by surfacing welding to restore its original size and improve the strength, hardness and impact resistance of the workpiece. At present, the wear-resistant materials used in the hammer of the hammer crusher are mainly high manganese steel, high chromium cast iron, etc.
[0003] Traditional high manganese steel materials have good toughness and work hardening ability, but the hardness value is low. When facing high impact, work hardening can occur, which greatly improves the hardness value of the material. Under small and medium impact conditions, due to the low degree of work hardening and very low hardness, the wear resistance of the material is very poor. Although high chromium cast iron materials have high hardness and good wear resistance, they have poor toughness and are prone to fracture under high impact conditions. Summary of the invention
[0004] In view of this, the present invention aims to overcome the defects in the prior art and proposes a hardening cladding flux-cored welding wire.
[0005] To achieve the above object, the technical solution of the present invention is achieved as follows: A hardened cladding flux-cored welding wire comprises a flux core and an outer sheath, wherein the flux core comprises the following components in mass fraction: 40%-60% high carbon ferrochrome, 0.5%-1.5% 75# ferrosilicon, 3%-7% electrolytic manganese, 6%-15% ferromolybdenum, 20%-45% titanium additive, 0.5%-2% arc stabilizer, 0.5%-1.5% rare earth additive, and the rest is iron powder, wherein the sum of the mass fractions of the components is 100%.
[0006] Furthermore, the flux-cored welding wire includes a flux core and an outer sheath, and the flux core includes the following components in mass fraction: 45%-55% high carbon ferrochromium, 0.6%-1.4% 75# ferrosilicon, 3%-7% electrolytic manganese, 6.5%-12% ferromolybdenum, 23%-40% titanium additive, 0.5%-2% arc stabilizer, 0.6%-1.4% rare earth additive, and the rest is iron powder, wherein the sum of the mass fractions of each component is 100%.
[0007] The particle size of each component of the flux-cored welding wire is 60 meshes to 200 meshes.
[0008] Furthermore, the titanium additive is at least one of titanium carbide and titanium-boron alloy.
[0009] Furthermore, the titanium additive is titanium carbide, the mass ratio of the titanium carbide to high carbon ferrochrome is 0.5-0.8:1, and the mass ratio of the titanium carbide to ferromolybdenum is 3.2-3.8:1.
[0010] Furthermore, the titanium additive is a titanium-boron alloy; the mass ratio of the titanium-boron alloy to high-carbon ferrochrome is 0.4-0.6:1.
[0011] Furthermore, the rare earth additive is at least one of rare earth ferrosilicon or yttrium-based heavy rare earth ferrosilicon.
[0012] Furthermore, the rare earth additive is rare earth ferrosilicon, and the mass ratio of the rare earth ferrosilicon to 75# ferrosilicon is 0.9-1.3:1.
[0013] Furthermore, the carbon content of the high carbon ferrochrome is 6.0wt%-9.0wt%, the chromium content is 60.0wt%-70.0wt%, and the balance is iron; the silicon content of the 75# ferrosilicon is 74wt%-80wt%, and the balance is iron; the manganese content of the electrolytic manganese is greater than or equal to 99.70wt%; the molybdenum content of the ferromolybdenum is 57wt%-60wt%, and the balance is iron.
[0014] Preferably, the carbon content in the high carbon ferrochrome is 8.2wt%, the chromium content is 60.69wt%, and the balance is iron; the silicon content in the 75# ferrosilicon is 74.3wt%, and the balance is iron.
[0015] Furthermore, the particle size of the powder in the high carbon ferrochrome is 80-120 meshes.
[0016] Furthermore, the flux core accounts for 18%-25% of the total weight of the welding wire; and the outer skin is a carbon steel cold-rolled steel strip.
[0017] The application of the work-hardenable cladding flux-cored welding wire in 80%Ar+20%CO2 gas shielded welding.
[0018] The welding conditions of the 80%Ar+20%CO2 gas shielded welding are: current 180A-320A; voltage 22V-30V; gas flow 20L / min-25L / min; thickness of each layer of deposited metal is greater than or equal to 2mm.
[0019] The application of the work-hardening surfacing flux-cored welding wire in the workpiece surfacing repair layer and the application of the work-hardening surfacing flux-cored welding wire in high manganese steel base material. The service environment is strong impact and high stress, the welded hardness is 40HRC-50HRC, and the hardness after work hardening is increased by 5HRC-15HRC.
[0020] The preparation method of the hardened cladding flux-cored welding wire comprises the following steps: rolling a carbon steel cold-rolled steel strip into a U-shaped groove, mixing and baking the powder and then adding it, and reducing the diameter by rolling and drawing to obtain the hardened cladding flux-cored welding wire. The welding wire is an 80% Ar+20% CO2 gas shielded welding wire with a diameter of 1.2 mm or 1.6 mm.
[0021] C: It forms carbides with alloy elements such as Cr and Mo. As the amount added in the powder increases, the hardness and wear resistance of the surfacing metal increase; but too high C content leads to increased brittleness of the alloy layer and decreased impact toughness. At the same time, since carbides are strong cathode phases of the matrix structure, they will accelerate the electrochemical corrosion of the surfacing metal and the base material.
[0022] Cr: Chromium can interact with carbon to generate carbides with higher hardness, thereby improving strength and hardness. These carbides can act as anti-wear phases, significantly improving the wear resistance of the cladding layer. At the same time, chromium has red hardness and high-temperature oxidation resistance, so that it can still maintain high hardness at high temperatures. Moreover, chromium can also be dissolved in the matrix, thereby improving the hardenability, hardness, wear resistance and corrosion resistance of the matrix structure.
[0023] Mo: It mainly exists in the weld metal in the form of eutectic carbides and solid solutions. Its role in the weld metal is to improve hardenability, produce solid solution strengthening, and inhibit temper brittleness; the formed carbides have an enhanced secondary hardening effect. It can not only improve the hardenability, strength and ductility of steel, but also greatly improve the impact toughness because molybdenum can eliminate or reduce the temper brittleness caused by other alloying elements. The distribution of molybdenum in the weld metal is mainly solid solution in the matrix to improve hardenability.
[0024] Si, Mn: Silicon and manganese are the most commonly used alloying elements in iron-based wear-resistant materials. They are dissolved in the matrix to improve the strength of the matrix. They have a greater affinity with O and are good deoxidizers, which are beneficial to reducing the oxygen content in the weld and preventing the formation of oxygen pores.
[0025] Ti: Titanium can preferentially precipitate TiC phase particles with a melting point of up to 3150°C and a microhardness of 3200 HV in situ in the liquid phase; fixing the free C atoms in the cladding metal reduces the probability of forming a brittle eutectic.
[0026] Rare earth elements: A small amount of RE has the effects of dehydrogenation, deoxidation, grain refinement, purification of impurities S and P, improvement of high-temperature oxidation resistance of cladding metal and enhancement of corrosion resistance; but when too much rare earth is added, it is easy to cause loose structure of cladding layer and reduce hardness.
[0027] Compared with the prior art, the present invention has the following advantages: The hardenable surfacing flux-cored welding wire of the present invention controls the composition of the surfacing metal by means of the powder components and contents, specifically: C, Cr, and Ti elements are transitioned into the surfacing metal by means of titanium carbide and high carbon ferrochrome, and Mo element is transitioned by means of ferromolybdenum; TiC is preferentially precipitated during the cooling process of the surfacing metal, and as the temperature decreases, the preferentially nucleated TiC will serve as the core of heterogeneous nucleation, so that Mo2C and Cr7C3 are attached to the TiC nucleus; appropriate contents of titanium carbide, high carbon ferrochrome, and ferromolybdenum will cause TiC to precipitate as the main carbide during the cooling process, and more Mo and Cr will be dissolved in the matrix, only a small amount of carbides will be formed, and the hardness of the matrix will be improved. degree, increasing the stability of the matrix; excessive addition of titanium carbide, high carbon ferrochrome and ferromolybdenum will cause the surfacing metal to form more residual austenite during the cooling process after welding, reducing the hardness of the surfacing metal; and the carbides of Mo and Cr will be more attached to TiC nucleation, resulting in coarse carbides, reducing the mechanical properties of the surfacing metal, and weakening the pinning effect of TiC, reducing the work hardening ability; lower additions of titanium carbide, high carbon ferrochrome and ferromolybdenum will reduce the in-situ precipitation of TiC in the surfacing metal and the solid solution strengthening produced by Mo and Cr, reducing the hardness of the surfacing metal and the effect of induced martensitic phase transformation caused by TiC after impact.
[0028] The work-hardenable surfacing flux-cored welding wire of the present invention has the characteristic of "self-strengthening" during use, and can be prepared into 80%Ar+20%CO2 gas shielded welding wires of 1.2mm and 1.6mm, with excellent surfacing process, stable arc, small spatter, beautiful weld bead shape, and convenient for on-site welding.
[0029] The titanium carbide in the work-hardenable cladding flux-cored welding wire of the present invention has a face-centered cubic lattice and can form a good coherent or semi-coherent relationship with the austenite matrix. It is well bonded to the matrix during the plastic deformation of the matrix under impact, and has stronger crack resistance. The cladding deposited metal contains fine dispersed titanium carbide (2μm-3μm), which plays a role of pinning dislocations and hindering the movement of dislocations during the impact wear hardening process. At the same time, plastic deformation causes a large number of deformation twins to be generated in the alloy. These deformation twins and dislocations are entangled around the titanium carbide, which increases the energy density and promotes the transformation of the austenite structure into twinned martensite and distribution around the titanium carbide. The rapidly increased martensite structure increases the hardness of the cladding metal by 5HRC-15HRC, and improves the wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A metallographic diagram of the welded microstructure of the work-hardenable cladding flux-cored welding wire according to an embodiment of the present invention; Figure 2 This is a metallographic diagram of the work-hardened cladding flux-cored welding wire according to an embodiment of the present invention after work-hardening. DETAILED DESCRIPTION
[0031] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0032] The present invention will be described in detail below with reference to the embodiments.
[0033] The components of the flux cores of each welding wire in Examples 1-4 and Comparative Examples 1-4 are shown in Table 1. The welding wire is obtained by rolling a carbon steel cold-rolled steel strip into a U-shaped groove, mixing and baking the flux powder, and then adding it, and then rolling and drawing to reduce the diameter. The diameter of the welding wire is 1.6 mm. The metallographic structure of the obtained welding wire as welded and the metallographic structure after work hardening are as follows: Figure 1-2 shown.
[0034] Table 1 Core components
[0035] The cladding flux-cored welding wires obtained in Examples 1-4 and Comparative Examples 1-4 were clad on high manganese steel base materials for 10 layers according to relevant standards, ensuring that the cladding metal composition was pure deposited metal and the welding shielding gas was 80% Ar + 20% CO2. The following tests were then performed: 1. Chemical composition test The chemical composition of the cladding layer was determined by direct reading spectrometer, and the specific values are shown in Table 2.
[0036] Table 2 Chemical composition of cladding metal
[0037] The workable and hardenable cladding flux-cored welding wire of the present invention controls the cladding metal composition by means of the powder component and content. Different amounts of powder added result in different chemical compositions of the deposited metal.
[0038] 2. Hardness test The hardness of the cladding layer was measured using a HBRV-187.5 Brinell hardness tester. Ten hardness points were taken for each cladding layer of each embodiment, and finally the average Rockwell hardness value of the cladding layer of the embodiment was obtained. The specific values are shown in Table 3.
[0039] Table 3 Metal hardness of cladding deposited metal
[0040] Appropriate content of titanium carbide, high carbon ferrochromium and ferromolybdenum will produce a better solid solution strengthening effect and form fine in-situ titanium carbide to improve the hardness of the surfacing metal. After adding titanium-boron alloy, B and C form boron carbide, which improves the initial hardness of the surfacing metal. The addition of rare earth elements will refine the grain size and improve the weld hardness.
[0041] 3. Hammer test After each example was tested for hardness, the cladding metal was hammered to provide impact stress, so that the surface of the cladding layer was work-hardened. The hardness of the cladding layer after hammering was measured using a HBRV-187.5 Brinell hardness tester, and 10 hardness points were taken for each example. Finally, the average Rockwell hardness value of the cladding layer of the example was obtained, and the specific values are shown in Table 4.
[0042] Table 4 Hardness of weld deposited metal after hammering
[0043] The increase in hardness is mainly due to the "self-strengthening" effect of in-situ titanium carbide. The formation of in-situ titanium carbide is mainly controlled by the titanium additives in the welding wire and the addition of high-carbon ferrochrome. The appropriate addition will form more fine in-situ titanium carbides, making them evenly dispersed in the matrix. After being subjected to impact stress, a large amount of twin martensite is formed around the titanium carbide. The rapidly increasing martensitic structure increases the hardness of the surfacing metal by 5HRC-15HRC.
[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A hardenable cladding flux-cored welding wire, characterized in that: The flux-cored welding wire comprises a flux core and an outer sheath, wherein the flux core comprises the following components in mass fraction: 40%-60% high-carbon ferrochrome, 0.5%-1.5% 75# ferrosilicon, 3%-7% electrolytic manganese, 6%-15% ferromolybdenum, 20%-45% titanium additive, 0.5%-2% arc stabilizer, 0.5%-1.5% rare earth additive, and the rest is iron powder, wherein the sum of the mass fractions of the components is 100%.
2. The hardenable cladding flux-cored welding wire according to claim 1, characterized in that: The flux-cored welding wire comprises a flux core and an outer sheath, wherein the flux core comprises the following components in mass fraction: 45%-55% high carbon ferrochromium, 0.6%-1.4% 75# ferrosilicon, 3%-7% electrolytic manganese, 6.5%-12% ferromolybdenum, 23%-40% titanium additive, 0.5%-2% arc stabilizer, 0.6%-1.4% rare earth additive, and the rest is iron powder, wherein the sum of the mass fractions of the components is 100%.
3. The hardenable cladding flux-cored welding wire according to claim 2, characterized in that: The titanium additive is at least one of titanium carbide and titanium-boron alloy.
4. The hardenable cladding flux-cored welding wire according to claim 3, characterized in that: The titanium additive is titanium carbide, the mass ratio of the titanium carbide to high carbon ferrochrome is 0.5-0.8:1, and the mass ratio of the titanium carbide to ferromolybdenum is 3.2-3.8:
1.
5. The hardenable cladding flux-cored welding wire according to claim 3, characterized in that: The titanium additive is titanium-boron alloy; the mass ratio of the titanium-boron alloy to high-carbon ferrochrome is 0.4-0.6:
1.
6. The work-hardenable cladding flux-cored welding wire according to claim 4, characterized in that: The rare earth additive is at least one of rare earth ferrosilicon or yttrium-based heavy rare earth ferrosilicon.
7. The work-hardenable cladding flux-cored welding wire according to claim 6, characterized in that: The rare earth additive is rare earth ferrosilicon, and the mass ratio of the rare earth ferrosilicon to 75# ferrosilicon is 0.9-1.3:
1.
8. The work-hardenable cladding flux-cored welding wire according to claim 2, characterized in that: The carbon content of the high carbon ferrochrome is 6.0wt%-9.0wt%, the chromium content is 60.0 wt%-70.0wt%, and the balance is iron; the silicon content of the 75# ferrosilicon is 74wt%-80wt%, and the balance is iron; the manganese content of the electrolytic manganese is greater than or equal to 99.70wt%; the molybdenum content of the ferromolybdenum is 57wt%-60wt%, and the balance is iron.
9. The work-hardenable cladding flux-cored welding wire according to claim 5, characterized in that: The particle size of the powder in the high carbon ferrochrome is 80-120 meshes.
10. The work-hardenable cladding flux-cored welding wire according to claim 2, characterized in that: The flux core accounts for 18%-25% of the total weight of the welding wire; the outer skin is a carbon steel cold-rolled steel strip.
Citation Information
Patent Citations
Impact abrasion resistant flux-cored wire used for hammer head of hammer crusher
CN101602150A
Titanium carbide ceramic-enhanced visible arc self-shielded flux-cored wire for high-chromium cast iron
CN102248325A
Abrasion-resisting surfacing flux-cored wire for coal milling roller
CN102554503A
Self-protection hardfacing flux-cored wire for repairing cement extrusion roller
CN110682032A
Wear-resistant and corrosion-resistant flux-cored wire for TIG-P surfacing of hydraulic bracket member
CN112122821A